1989
DOI: 10.1248/cpb.37.1117
|View full text |Cite
|
Sign up to set email alerts
|

A new pharmacological testing method. Different effects of levamisole and the serum of mice orally treated with levamisole on mitogenic activity of lipopolysaccharide.

Abstract: The direct addition of levamisole to murine splenic lymphocytes had no effect on the mitogenic activity of lipopolysaccharide. However, the addition of serum of mice orally treated with levamisole increased the mitogenic activity, and this increased activity using serum was similar to the result obtained in an in vivo experiment. These results suggest that the new in vitro experimental method using serum may be able to reproduce the in vivo effect of drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Henceforth, it was also confirmed that the direct addition of levamisole to murine splenic lymphocytes had no effect on the mitogenic activity of LPS. However, the addition of serum from mice orally treated with levamisole increased the mitogenic activity, and this increased activity using serum was similar to the result obtained in an in vivo experiment (Amagaya et al, 1989). These suggest that the new in vitro experimental method using serum may be able to reproduce the in vivo effect of drugs and the new pharmacological testing method pro- Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Henceforth, it was also confirmed that the direct addition of levamisole to murine splenic lymphocytes had no effect on the mitogenic activity of LPS. However, the addition of serum from mice orally treated with levamisole increased the mitogenic activity, and this increased activity using serum was similar to the result obtained in an in vivo experiment (Amagaya et al, 1989). These suggest that the new in vitro experimental method using serum may be able to reproduce the in vivo effect of drugs and the new pharmacological testing method pro- Fig.…”
Section: Discussionsupporting
confidence: 72%
“…The disruption of gene expression can be corrected by LW in the hippocampal formation of SAMP8 (Cheng et al, 2007). Serum pharmacology has proven to be an effective method to study TCM prescriptions (Amagaya et al, 1989;Iwama et al, 1987;Zhang et al, 2000). According to the concept of serum pharmacology, serum from animals administered a TCM prescription orally is widely used to uncover the mechanisms of TCM prescriptions that contain too many unidentified compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, serum pharmacology was put forward and proved to be effective in pharmacological research on TCM prescription (Iwama et al, 1987;Amagaya et al, 1989;Zhang et al, 2000). According to the concept of serum pharmacology, serum from animals administered with TCM prescription orally is widely used to uncover the mechanism of TCM prescription that content too many unidentified compounds.…”
Section: Introductionmentioning
confidence: 99%